Governing "European values" inside data flows - Kristina Irion; Mira Burri; Ans Kolk; Stefania Milan (Internet Policy Review, 2021)
This editorial introduces ten research articles, which form part of this special issue, exploring the governance of "European values" inside data flows. Protecting fundamental human rights and critical public interests that undergird European societies in a global digital ecosystem poses complex challenges, especially because the United States and China are leading in novel technologies. We envision a research agenda calling upon different disciplines to further identify and understand European values that can adequately perform under conditions of transnational data flows.
Keywords: 300; European values; European Union; Digital connectivity; Data flows; Artificial intelligence; Human rights; Societal values; Personal data protection; Public policy; Internet governance; Data governance